Controllable Decomposition in Ahm Crystals in Ultraviolet Radiation - Rodzevich A. P. Aleksandr Pavlovich; Ivakhnyuk S. V.; Krasheninin V. I.; Gazenaur V. I.; Marenets V. G. (Materials Science in Mechanical Engineering, 2015)
Title screen